2017
DOI: 10.1186/s12864-016-3476-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive CircRNA expression profile and selection of key CircRNAs during priming phase of rat liver regeneration

Abstract: BackgroundRat liver regeneration (LR) proceeds along a process of highly organized and ordered tissue growth in response to the loss or injury of liver tissue, during which many physiological processes may play important roles. The molecular mechanism of hepatocyte proliferation, energy metabolism and substance metabolism during rat LR had been elucidated. Further, the correlation of circular RNA (circRNA) abundance with proliferation has recently been clarified. However, the regulatory capacity of circRNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 64 publications
1
85
1
Order By: Relevance
“…The existing papers mainly focus on the field of primary liver cancer . However, other studies have found that circRNA is associated with non‐alcoholic fatty liver and liver regeneration mechanisms . Recently, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing papers mainly focus on the field of primary liver cancer . However, other studies have found that circRNA is associated with non‐alcoholic fatty liver and liver regeneration mechanisms . Recently, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…4 However, other studies have found that circRNA is associated with non-alcoholic fatty liver and liver regeneration mechanisms. 5,6 Recently, Chen et al reported for the first time that circRNA is involved in HSC activation. The researchers used microarray technology to analyze the differentially expressed circRNAs in a model of radiation-induced HSC activation and found that, compared with the normal control group, there were 179 upregulated circRNAs and 630 downregulated circRNAs in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between circRNAs and the brain, liver and heart have been recognized. Recently, the role of circRNAs in cancer was also highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been verified that circRNAs work through various ways including acting as miRNAs sponge, regulating transcription by interacting with small nuclear ribonucleoproteins (snRNP), recruiting RNA polymeraseII, interacting with proteins, and coding protein [7]. We had shown that 159 circRNAs were differentially expressed (DE) in the priming phase after PH [8]. In the present study, we aimed primarily to investigate the potential mechanism of circRNAs regulating the proliferation phase after 2/3 PH in rats.…”
Section: Introductionmentioning
confidence: 97%